Juros e inflação da economia brasileira na perspectiva do Novo Consenso Macroeconômico e Teoria Fiscal de Preços - Gonçalves, Alécio Romero (2018)
The present study seeks to analyze the relationship of the nominal interest rate and inflation in the Brazilian economy after the adoption of the inflation targeting system for the period from December 2001 to September 2017. To this end, it is investigated whether monetary policy responds to the proposal of the New Macroeconomic Consensus (NMC), in addition, it is also proposed to examine the reaction of the nominal interest rate to shocks in inflation, as well as the reaction of inflation to shocks in the nominal interest rate. Finally, the Fiscal Theory of the Price Level (FTPL) was tested in order to verify if inflation could be linked to fiscal issues. For the analysis, the time series econometrics, the Ordinary Least Squares method is used to verify the NMC. And, to verify the reaction of the nominal interest rate and inflation, as well as to test the FTPL, the method of Self-Regressive Vectors is used. It was verified that the Brazilian monetary policy conforms to the NMC, but inflation does not react in the way the theory expects. For FTPL, it was not possible to identify it for the Brazilian case. The results may indicate that Brazilian inflation is not driven, for the most part, by demand and, not so much, by fiscal matters.